ANALISIS UJI KETAHANAN LELAH BAJA KARBON SEDANG AISI 1045 DENGAN HEAT TREATMENT (QUENCHING) DENGAN MENGGUNAKAN ALAT ROTARY BENDING - Teguh Sugiarto; . Zulhanif; . Sugiyanto (Jurnal Ilmiah Teknik Mesin, 2013)
Fatigue is the one of the main cause from of the material failure. The main of cause failure 90 % caused fatigue.   Fatigue is material sructure process changes that is caused by repeatly load (stress or shear) in a long period of time so it occured crack or break. The reason of this research is to analyze of the fatigue strength medium carbon steel type AISI 1045 with variaton of shaft rotation on rotary bending machine. Fatigue test applied on medium carbon steel  type AISI 1045 without heat treatment. This research was conducted with variation of shaft rotation 2880 rpm and continued with load variation 20%, 30%, 40%, 50% and 60 % from material UTS. Specimen that used according ASTM E466 spesimen made by lathe machine. Fatigue test is using by rotary bending machine type fatigue test machine.Keywords:Fatigue test, rotary bending, medium carbon steel  AISI 1045.